Anne-Marie AUTISSIER, Javier GÓMEZ-MONTERO, Anxo ABUÍN, Victor A. FERRETI, Rubén Lois GONZÁLEZ y Rainer WEHRHAHN, eds., "Urban Dynamics: Conflicts, Representations, Appropriations and Policies". Berlín, Peter Lang, 2018, 356 pp. - Tamames Gala, Cristina (Tropelías. Revista de Teoría de la Literatura y Literatura Comparada, 2019)
Reseña de Anne-Marie AUTISSIER, Javier GÓMEZ-MONTERO, Anxo ABUÍN, Victor A. FERRETI, Rubén Lois GONZÁLEZ y Rainer WEHRHAHN, eds., "Urban Dynamics: Conflicts, Representations, Appropriations and Policies". Berlín, Peter Lang, 2018, 356 pp.